2022
DOI: 10.3390/ijms23020671
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S Impairs Invasion and Proliferation of Extravillous Trophoblasts Cells by Interfering with Epidermal Growth Factor Receptor Signaling

Abstract: The placenta supports fetal growth and is vulnerable to exogenous chemical exposures. We have previously demonstrated that exposure to the emerging chemical bisphenol S (BPS) can alter placental endocrine function. Mechanistically, we have demonstrated that BPS interferes with epidermal growth factor receptor (EGFR) signaling, reducing placenta cell fusion. Extravillous trophoblasts (EVTs), a placenta cell type that aids with vascular remodeling, require EGF to invade into the maternal endometrium. We hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Notably, exogenous EGF slightly upregulated EGFR phosphorylation also in Mel 599 P cells, suggesting that the EGFR constitutively expressed by these cells is functional. EGF stimulation triggered downregulation of EGFR, in line with literature data reporting degradation of activated EGFR (54)(55)(56)(57)(58)(59)(60)(61). Independent of the degree of constitutive EGFR phosphorylation, activation of the AKT pathway emerged as a common feature of VR cells, as demonstrated by the increased phosphorylation of AKT1 found in 3 out of 4 VR cell cultures as compared to their P isogenic cells.…”
Section: Signaling Correlates Of De Novo Egfr Expression In CM Cells ...supporting
confidence: 88%
“…Notably, exogenous EGF slightly upregulated EGFR phosphorylation also in Mel 599 P cells, suggesting that the EGFR constitutively expressed by these cells is functional. EGF stimulation triggered downregulation of EGFR, in line with literature data reporting degradation of activated EGFR (54)(55)(56)(57)(58)(59)(60)(61). Independent of the degree of constitutive EGFR phosphorylation, activation of the AKT pathway emerged as a common feature of VR cells, as demonstrated by the increased phosphorylation of AKT1 found in 3 out of 4 VR cell cultures as compared to their P isogenic cells.…”
Section: Signaling Correlates Of De Novo Egfr Expression In CM Cells ...supporting
confidence: 88%
“…Conversely, when proliferation is excessively stimulated, CT differentiation becomes inhibited, resulting in the impairment of ST and EVT formation. A previous study demonstrated that BPS does not affect the proliferation of HTR8/SVneo cells (Ticiani et al, 2022). This cell line is immortalized and has characteristics of the non-proliferative extravillous trophoblast cells which are completely different from the progenitor CTs or TSCs.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, it is imperative to conduct a comprehensive examination of the potential toxic effects of this chemical to ascertain whether it is safe to the human body and pregnancy. It has been demonstrated that BPS affects EGF signaling in human trophoblast cells (Ticiani et al, 2022), impairs endocrine functions in the sheep placenta (Gingrich et al, 2018), and induces morphological defects in the junctional zone of the mouse placenta (Mao et al, 2020). However, the impacts of BPS on human placenta development remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Data show that exposure to endocrine-disrupting chemicals like bisphenols A and their substitutions (BPS, BPF, TBBPA, BADGE) affect early development stages. Early developmental involves implantation, trophoblast invasion, and remodelling are modulated by BPA ( 16 , 17 , 26 32 ), BPS ( 33 , 34 ), BPF ( 32 , 34 ), and TBBPA ( 35 ) exposure. The trophoblast Syncytialization and nutrient exchange across the placenta are affected by BPA ( 22 , 23 ), and BPS ( 36 ) exposure.…”
Section: Exposure To Endocrine Disruptors Affects Maternal Endocrine ...mentioning
confidence: 99%
“…Single-headed arrow indicates an independent study reported so far available from the PubMed database. BPA, Bisphenol A ( 23 , 24 , 26 28 , 38 ); BPS, Bisphenol S ( 25 , 33 , 36 , 42 , 150 , 151 ); BPF, Bisphenol F ( 34 , 39 ); TBBPA, Tetrabromo Bisphenol A ( 35 , 40 , 43 , 152 , ( 44 ); BADGE, Bisphenol A diglycidyl ether ( 45 ).…”
Section: Endocrine-disrupting Chemicals Induce Endocrine Dysfunction ...mentioning
confidence: 99%